Peningkatan Hasil Belajar IPA Melalui Media Miniatur Pada Anak Tunanetra Kelas I Di SLB Negeri Merauke - Reski Dwiyanti; Kasmawati Kasmawati; Syamsuddin Syamsuddin (JURNAL ORTO DIDAKTIKA, 2023)
The problem in this study departs from the low ability of blind children to recognize and classify animal species. Blind is a term for those who experience obstacles in vision, both totally blind and low vision. Therefore we need a learning that is able to improve the ability to recognize and classify the types of animals, namely by using miniature media. The purpose of this research is to improve the ability to recognize and classify animal species through miniature media for blind children. The subject in this study was a blind child who was classified as Low Vision Class IV at the Merauke State SLB. This study uses the Single Subject Research (SSR) experimental method, which focuses on individuals as research samples with an A – B – A design. Data collection techniques used are tests and actions. The data analysis technique in this study uses descriptive statistics and the results are displayed in graphical form. The results of the research on the subject showed an increase in the percentage of ability to recognize and classify animal species before and after the intervention. The mean level in baseline phase 1 was 20, the mean level in intervention was 74.7 and the mean level in baseline phase 2 was 84.4. This shows that there was an increase in the mean level of 86.6 from baseline 1 to baseline 2. It can be concluded that using miniature media can improve the ability to recognize and classify animal types in blind children.